Prevalence of areca nut chewing in the middle school-going children of Indore, India - Ashok Khandelwal; Vishal Khandelwal; Mainak K Saha; Sushma Khandelwal; Sai Prasad; Suparana G Saha (Wolters Kluwer Medknow Publications, 2012)
Objectives: To assess areca nut chewing habit among middle school-aged children in Indore, India. Areca nut is chewed by itself, and in various scented preparations. It is associated with carcinogenesis, foreign body aspiration in children, and oral submucous fibrosis and may aggravate asthma. Materials and Methods: A retrospective collection of data to evaluate the prevalence of areca nut chewing among 3896 children was done. A simple random sampling was done. Children of both sexes were included in this study. Results: 27.06% of the school-going children (1054/3896) had areca nut chewing habit. More boys chewed areca nut than girls (2:1). 45.42% of school going children of rural area pander to areca nut chewing habit, whereas in urban area 20.09% children are indulged. Government school children are more involved in areca nut chewing habit. 81.02% of the children used sweetened and flavoured form of areca nut. The majority of the users were not aware of harmful effects that the use of areca nut might be harmful for health Conclusion: To diminish the use of areca nut, the Indian Government should consider limiting trade, advertising, and actively communicating its health risks to the public and should deem heavy taxes on it.